Analyze The Characteristic of Rainfall and Intensity Duration Frequency (IDF) Curve at Lampung Province - Susilowati SUSILOWATI (International Conference on Engineering and Technology Development (ICETD), 2012)
This research was done to analyze the characteristic of rainfall based the short term duration of rainfall data at BMG Maritim Lampung station, BMG Raden Inten II Bandar Lampung station, Masgar Tegineneng Climatology station and Kotabumi Geophysical station. From the results of the research intensity duration frequency (IDF) curve will be made based on: (1) Analysis of rain distribution frequency of short term rainfall data from each statios. (2) Analysis of rainfall intensity for every rain duration in particular measurement uses Van breen intensity method and Hasper der weduwen intensity method then least square (kuadrat kecil) is used to calculate rainfall intensity approach by Talbot, Sherman and Ishiguro formulaâs, the purpose is to determine the equality of rainfall intensity to targeted region. From the result of the research, it could be summarized as follows ;(1) The data of rainfall used is short term rainfall data (5, 10, 15, 30, 45, 60, 120 minutes, 3 hours, 6 hours and 12 hours) and as annual maximum series, (2) Type of distribution that appropriate with all observation station is Log Pearson Type III Distribution, (3) The rainfall intensity of Van Breen method used Talbot equality, it is used as reference to form IDF curve. The intensity equality was valid only to data of rain in all observation year at every station. (4) The IDF Curve showed that high rainfall intensity happen in short duration (5) the IDF curve can be used to determine planning flood by using rational method.